On the problem of determination of dynamical reaction forces and components of internal forces of a system of links - Sanh, Do (Vietnam Journal of Mechanics, 1981)
In this paper it is presented two problems. By the results of the first problem we obtain a simple method for determinating the hinge reaction forces of a system of n links. Using th2 results of the second problem it is possible to easily determine the components of internal forces at any section of a certain link.